2020
DOI: 10.1289/ehp5779
|View full text |Cite
|
Sign up to set email alerts
|

Daily Temperature and Bacillary Dysentery: Estimated Effects, Attributable Risks, and Future Disease Burden in 316 Chinese Cities

Abstract: BACKGROUND: Bacillary dysentery (BD) remains a significant public health issue, especially in developing countries. Evidence assessing the risk of BD from temperature is limited, particularly from national studies including multiple locations with different climatic characteristics. OBJECTIVES: We estimated the effect of temperature on BD across China, assessed heterogeneity and attributable risks across cities and regions, and projected the future risk of BD under climate change. METHODS: Daily BD surveillanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 43 publications
(62 reference statements)
1
26
0
Order By: Relevance
“…Measures of attributable risk are an integral part of epidemiological analyses, particularly when aimed at the planning and evaluation of public health interventions [26,27,32]. It was presented in our results that the overall attributable fraction of HFMD incidence due to hot temperatures (39.55%) was significantly higher than that due to cold temperatures (5.23%).…”
Section: Discussionmentioning
confidence: 60%
“…Measures of attributable risk are an integral part of epidemiological analyses, particularly when aimed at the planning and evaluation of public health interventions [26,27,32]. It was presented in our results that the overall attributable fraction of HFMD incidence due to hot temperatures (39.55%) was significantly higher than that due to cold temperatures (5.23%).…”
Section: Discussionmentioning
confidence: 60%
“…Daily mean relative humidity (RHmean), as potential confounding variables, was modeled as a natural cubic spline (ns) with 3 degrees of freedom. DOW stands for day of the week, which was entered as a categorical variable, and β is the coefficient of DOW [27,[29][30][31].…”
Section: Methodsmentioning
confidence: 99%
“…Characteristics of eligible studies Figure 1 shows a ow chart of the literature search and screening process. A total of 27 studies met our inclusion criteria (Cheng et al 2017;D'Souza et al 2008;Dewan et al 2013;Gao et al 2020;Hao et al 2019;Hashizume et al 2008;Hu et al 2019;Li et al 2016;Li et al 2019;Li et al 2014;Li et al 2013;Liu et al 2020;Luque Fernández et al 2009;Qiang et al 2013;Thindwa et al 2019;Traerup et al 2011;Wang et al 2019a;Wang et al 2019b;Wang et al 2021;Wang et al 2019c;Wang et al 2018;Wang et al 2011;Wu et al 2018;Xu et al 2017;Zhang 2019;Zhang et al 2021), with a total population of more than 7.07 million. Among the results of these models, not only some studies report the single-day effect of temperature (17 studies reported on the single-day effect of temperature, and a total of 28 estimates and effect intervals were collected), but some studies report the cumulative effect of temperature over multiple days (16 studies reported on the cumulative effect of temperature, and a total of 30 estimates and effect intervals were collected).…”
Section: Resultsmentioning
confidence: 99%